CD137在北方地区经典型霍奇金淋巴瘤中的表达及辅助病理鉴别诊断价值探讨 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To investigate the expression of CD137 in HRS cells of classical Hodgkin Lymphoma (cHL), and its application in the pathological differential diagnosis. METHODS: 54 cases of cHL with “HRS” cells, and 55 cases of non-cHL with “HRS-like” cells as control group were collected. “HRS” cells and “HRS-like” cells rich areas in slides were selected from relevant groups to produce two tissue microarrays. This study focused solely on “HRS” cells and “HRS-like” cells, immunohistochemical staining for antibodies including CD30, CD15, CD20, CD3, and PAX5 were performed on CHL cases, CD137 (clone BBK-2) immunostaining and EBER in situ hybridization were detected in both groups. RESULTS: All cHL cases aged 22.0–68.0 (median 45.5) years with the male to female ratio as about 1.7∶1 primarily involved lymph nodes; while in the control group, 54 cases aged 12.0–81.0 (median 50.0) years with male∶female=1.9∶1 primarily located in nodes with only 1 case in skin. In the cHL group, CD30, CD15, CD20 and CD3 were positive in 100.0%, 70.4%, 18.5% and 0 cases in order, and PAX5 showed weak to moderate positive in 70.4% cases; the positive rate of EBER was 25.9% in cHL group, and 21.8% in the control group; The CD137 positive rates were 57.4% in cHL and 14.5% in the control groups with a significant difference (P<0.001). There were no significant differences when CD137 expressions were further compared according to the differences in age [elder group (aged 60) /non elderly group], gender (male/female), EBV infection (yes/no), histological subtype and the expression of those major diagnostic markers (positive/negative) in either cHL or control groups (all P valued>0.05). The positive rates of CD137 expression in cHL were significantly different when sub-grouped according to accession year before or after 2013 (39.4% vs 85.7%, P=0.001); However, no difference was seen in the control group (12.5% vs 16.1%, P=0.705). For those cases after 2013, the CD137 positive ratio of cHL group was more significantly different with the control one (85.7% vs 16.1%, P<0.001). CONCLUSION: Frequent expression of CD137 in “HRS” cells of cHL cases from Northern China could be detected by IHC method, while the CD137 expression was much lower in “HRS-like” cells of the control group. The positive rate of CD137 expression by immunohistochemical staining significantly increased in this cohort stored less than 3 years, which might be more reliable. CD137 might be potentially applied on pathological differential diagnosis of cHL.